Entre novas técnicas e velhos costumes, uma abordagem histórica do perímetro irrigado Curu-Paraipaba-CE (1974 – 1990) - Medeiros, Francisco Hugo Sousa de (2024)
The creation of the Perímetro Irrigado Curu-Paraipaba in 1974, as part of agribusiness development, modified the rural landscape and the daily routines of workers, which affected the social dynamics of the region. This study addresses how these changes impacted the lives of farmers in the Perímetro Irrigado Curu-Paraipaba. Following various attempts to implement irrigation as a viable project to combat drought, the National Irrigation Policy (PNI) aimed to expand investments to integrate the Northeast into the national market, introducing agricultural modernization and bringing significant transformations to both the rural environment and the farmers' way of life. Agricultural modernization became a strategic project for development, aiming to enhance production through the construction of irrigation perimeters, seeking to develop high-productivity irrigated agriculture. This initiative intended to shift from traditional, nature-dependent, subsistence agriculture to a mechanized agriculture oriented towards large capital. Understanding how this mechanization of rural space altered the customs and living conditions of farmers, through the analysis of colonists' daily lives and official documents, is a key focus of this research. The study utilizes documents produced by the National Department of Works Against Drought (DNOCS), site visits, observations, and photographs of the Perímetro Irrigado Curu-Paraipaba, interviews with irrigators and residents of the region, as well as a literature review of academic research.